Handbook of MEMS for wireless and mobile applications - Uttamchandani, Deepak (Woodhead Publishing series in electronic and optical materials ;, 2013)
Provides a comprehensive overview of radio frequency (RF) MEMS technologies and explores the use of these technologies over a wide range of application areas.